2023
DOI: 10.5853/jos.2022.03468
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Women: A Review Focused on Epidemiology, Risk Factors, and Outcomes

Abstract: Stroke is a particularly important issue for women. Women account for over half of all persons who experienced a stroke. The lifetime risk of stroke is higher in women than in men. In addition, women have worse stroke outcomes than men. Several risk factors have a higher association with stroke in women than in men, and women-specific risk factors that men do not have should be considered. This focused review highlights recent findings in stroke epidemiology, risk factors, and outcomes in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 144 publications
0
13
0
3
Order By: Relevance
“…Studies have shown that stroke incidence is higher in women, who often experience poorer outcomes than men (Bushnell & Kapral, 2022;Xu et al, 2022;Yoon & Bushnell, 2023). Therefore, post-stroke support systems must be specifically tailored to women's unique needs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that stroke incidence is higher in women, who often experience poorer outcomes than men (Bushnell & Kapral, 2022;Xu et al, 2022;Yoon & Bushnell, 2023). Therefore, post-stroke support systems must be specifically tailored to women's unique needs.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether the age and gender of patients can influence the expression of specific genes linked to the inflammation-caused exaggeration of ischemic damage and promotion of regeneration and functional recovery. Further research is needed to fully understand the properties of monocytes from age and sex perspectives [44].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is a multifactorial and complex neurological disorder characterised by the sudden interruption of blood supply to the brain, resulting in a cascade of cellular and molecular events that leads to tissue damage and subsequent neurological deficits (1) . The worldwide incidence of stroke is estimated to be 17 million cases annually (2) .…”
mentioning
confidence: 99%